Treatment with the apoptosis inhibitor Asunercept reduces clone sizes in patients with lower risk Myelodysplastic Neoplasms - Streuer, Alexander; Jann, Johann-Christoph; Boch, Tobias; Mossner, Maximilian; Riabov, Vladimir; Schmitt, Nanni; Altrock, Eva; Xu, Qingyu; Demmerle, Marie; Nowak, Verena; Obländer, Julia; Palme, Iris; et al. (Annals of hematology, 2024)
In low-risk Myelodysplastic Neoplasms (MDS), increased activity of apoptosis-promoting factors such as tumor necrosis factor (TNFα) and pro-apoptotic Fas ligand (CD95L) have been described as possible pathomechanisms leading to impaired erythropoiesis. Asunercept (APG101) is a novel therapeutic fusion protein blocking CD95, which has previously shown partial efficacy in reducing transfusion requirement in a clinical phase I trial for low-risk MDS patients (NCT01736436; 2012-11-26). In the current study we aimed to evaluate the effect of Asunercept therapy on the clonal bone marrow composition to identify potential biomarkers to predict response. Bone marrow samples of n = 12 low-risk MDS patients from the above referenced clinical trial were analyzed by serial deep whole exome sequencing in a total of n = 58 time points. We could distinguish a mean of 3.5 molecularly defined subclones per patient (range 2-6). We observed a molecular response defined as reductions of dominant clone sizes by a variant allele frequency (VAF) decrease of at least 10% (mean 20%, range: 10.5-39.2%) in dependency of Asunercept treatment in 9 of 12 (75%) patients. Most of this decline in clonal populations was observed after completion of 12 weeks treatment. Particularly early and pronounced reductions of clone sizes were found in subclones driven by mutations in genes involved in regulation of methylation (n = 1 DNMT3A, n = 1 IDH2, n = 1 TET2). Our results suggest that APG101 could be efficacious in reducing clone sizes of mutated hematopoietic cells in the bone marrow of Myelodysplastic Neoplasms, which warrants further investigation.
Online veröffentlicht: 27. Februar 2024
Gesehen am 03.02.2025